Strategic management confrontation to transformation - Volberda, Henk W.; Heij, Kevin; Hollen, Rick; Pereira, Joana; Sidhu, Jatinder (Sage, 2024)
"Change challenges leaders, managers and strategists, and demands that they confront their new realities. This book offers a fresh, reader-friendly, challenging and provocative perspective on strategic management, detailing the 'confront-sense-choose-transform' process stages, which begins with confronting business challenges and addressing several strategy tensions between theory and practice. In the continued quest for temporary advantage organizations need strategic capabilities to sense, choose and transform. The clear process stage model of strategic management and an action-oriented why-how structure help students and practitioners of strategy - from first year undergraduates to Executive MBA - to confront the new 'now' - fast, iterative and innovative. With each chapter dedicated to up-to-date theories of strategic management and specific practices from businesses around the world, illustrations and sets of activities that trigger the senses with rich supporting materials, this book will help grow readers' knowledge and experience of developing and implementing strategy in the real world"--